Literature Reviews of Internal Aspects of Individual Taxpayers That Influence Tax-Paying Compliance - Dyah Pita Sari, Ratna Hindria (Syntax Literate, 2021)
Studies on individual taxpayer compliance have been carried out. Several internal factors from within the taxpayer can affect taxpayer compliance. In this study, researchers will identify any internal factors affecting taxpayer compliance in paying taxes. Researchers reviewed 20 articles related to internal factors that can affect tax compliance. Such internal factors include tax morale, education level, income level, age, and gender. According to the 20 articles, there are still inconsistencies. Several studies have stated that these internal factors affect taxpayer compliance. Another study states that the internal factors did not affect taxpayer compliance.